Global Trends in the contribution of University Lifelong Learning in shaping the labour markets and its applicability to EU - An IACEE Perspective - Alfredo Soeiro (2017)
International Association for Continuing Engineering Education (IACEE) supports and enhances lifelong learning in engineering around the globe. Located worldwide, the academic and professional members of IACEE often engage in creating professional higher education programs that provide the relevant content in appropriate mode of delivery to advance the knowledge of engineers and scientists, thus providing professional development for upskilling them. In the workshop, eight members from five countries will reflect upon their experiences in their organizations and critically analyze the trends in Australia, Mexico and the United States of America, and will compare those with the trends in Norway and Portugal, the two European countries represented in this workshop. The panelists/presenters will also ask the questions to the participants and will engage in conversations. In this interactive workshop, the participants will have the opportunity to share their observations in the evolutionary role of ULLLs in shaping the labour market, and how that has influenced the regional and national economic development.